THE ROLE OF PROTOCOL BIOPSIES IN EARLY PERIOD AFTER KIDNEY TRANSPLANTATION - V. A. Suhorukov; Y. L. Yushinskis; I. Shtrumfa; R. L. Rozental (Вестник трансплантологии и искусственных органов)
46 protocol graft biopsies with the subsequent histological examination were performed in 39 patients after kidney transplantation. In 20 patients with stable graft function acute subclinical rejection were revealed in 12 (60%) with the following steroid therapy. In 19 patients with delayed kidney graft function acute rejection was revealed in 13 (68,4%). Treatment by steroids was successful and function renewed. Our results showed that protocol biopsy is a safe and reliable method that allows to recognize such kidney graft pathology as subclinical rejection and to perform its treatment in time.